3 a + b = 10
-
2 a + 4 b = 0
__________
3 a - 2 a + b - 4 b = 10 - 0
a - 3 b = 10
Add 3 b to both sides
a = 10 + 3 b
Substitute this value in one of equations ( never mind wich ). In this case in first equation.
3 a + b = 10
3 ( 10 + 3 b ) + b = 10
3 ∙ 10 + 3 ∙ 3 b + b = 10
30 + 9 b + b = 10
30 + 10 b = 10
Subtract 30 to both side
10 b = - 20
Divide both sides by 10
b = - 2
a = 10 + 3 b
a = 10 + 3 ∙ ( - 2 )
a = 10 - 6
a = 4
Solution:
a = 4 , b = - 2
Proof:
3 a + b = 10
3 ∙ 4 + ( - 2 ) = 10
12 - 2 = 10
10 = 10
2 a + 4 b = 0
2 ∙ 4 + 4 ∙ ( - 2 ) = 0
8 - 8 = 0
0 = 0
3a+b=10, 2a+4b=0
5 answers
Use substitution,
from the first: b = 10-3a
into the second
2a+4b=0
2a + 4(10-3a) = 0
2a + 40 - 12a = 0
-10a = -40
a = 4
then b = 10-4b = 10-16 = -6
from the first: b = 10-3a
into the second
2a+4b=0
2a + 4(10-3a) = 0
2a + 40 - 12a = 0
-10a = -40
a = 4
then b = 10-4b = 10-16 = -6
Mathematics
I luv dis
A=4,b=-2